Relationship between body composition, anthropometry and physical fitness in under-12 soccer players of different positions - Aurélio, Jorge (2018)
This study aimed to investigate the relationship between body composition, anthropometry and physical fitness in under-12 soccer players who play in different positions. Eighteen players underwent a battery of tests, in body composition and anthropometry significant differences were observed in weight (44.0 ± 4.6 vs. 35.6 ± 4.0 kg; p = 0.04) and body mass index (18.1 ± 1.0 vs. 16.1 ± 1.2 kg/cm2; p = 0.01) between defensive and midfield players. In physical fitness differences occurred between the results in handgrip strength between defenders and forwards (21.3 ± 2.8 vs. 25.4 ± 3.7 kg; p = 0.04) and midfielders and forwards (20.5 ± 2.0 vs. 25.4 ± 3.7 kg; p = 0.04). Correlations occurred in the soccer defenders between body fat and the result of the agility test (r = -0.85, p <0.01). In the midfield players there was a correlation between height and countermovement jump (r = -0.91, p <0.05). It was also observed in the forward players a correlation between speed and agility (r = 0.88, p <0.05) and between agility and other two variables, body fat (r = 0.84, p <0.05) and handgrip strength (r = -0.93, p <0.01). A positive relationship between the aerobic performance and countermovement jump was also observed (r = 0.96, p <0.01), and a negative relationship between the aerobic performance and weight (r = -0.88, p <0.05). Under-12 soccer players should be involved in specific strength training and functional performance evaluated using scientific instruments for talent identification and training control.